Pengaruh Praktik Pengalaman Lapangan Terhadap Kesiapan Menjadi Guru Profesional - Fiskia Rera Baharuddin; Andi Muadz Palerangi (PINISI :Journal of Teacher Professional, 2020)
The research aims to determine the effect of the practice of field experience on readiness to become a professional teacher. This study uses a quantitative approach with a total of 70 students majoring in mechanical engineering education at UNM. Data collection techniques using questionnaires and documentation. The instrument validity was tested using Product Moment correlation and the reliability test used the Cronbach Alpha formula. Data were analyzed using descriptive statistics, prerequisite tests and regression analysis. The results showed that there was a significant positive effect between the practice of field experience on the readiness to become a professional teacher of students majoring in PTM FT-UNM with sig. 0,000 <0.05. The results of the regression analysis showed that the practice of field experience had a significant effect on teacher readiness of 58.7%. The results of this study are expected to be followed up as a reference and evaluation material in improving the quality of education.